Small Multi-Band Rectangular Dielectric Resonator Antennas for Personal Communication Devices - Hemn Younesiraad; Mohammad Bemani; Saied Nikmehr (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The design of a novel rectangular dielectric resonator antenna (DRA) for multi-band application has been presented in this paper. The presented antenna has been composed of very low cost and relatively low dielectric constant substrate materials while three-segment thin dielectrics with different sizes have been used and separated by two metal plates in order to set the four diﬀerent frequency bands. The proposed quad-band antenna operates at 2.4/3.5/5.2 & 5.8 GHz. The radiation pattern, gain and VSWR of this antenna show very good operation for this antenna in all frequency bands. The ﬁrst method based on ﬁnite element method (FEM) and the second one based on ﬁnite integral technique (FIT) have been used to analyze antenna structure, and subsequently the Genetic Algorithm (GA) has been applied by using HFSS simulator to obtain the optimized parameters.DOI:http://dx.doi.org/10.11591/ijece.v4i1.4576